1998
DOI: 10.1103/physrevb.57.5715
|View full text |Cite
|
Sign up to set email alerts
|

Infrared activity in the Aurivillius layered ferroelectricSrBi2Ta2O

Abstract: Experimental studies were carried out on infrared-active phonons in the Aurivillius ferroelectric SrBi 2 Ta 2 O 9 ͑SBT͒, using reflectivity measurements ͑down to 200 cm Ϫ1 ͒ and transmission measurements ͑down to 100 cm Ϫ1 ͒ on crystals, pellets, and thin films. An analysis was done of the contrasting consequences of the competing orthorhombic and pseudotetragonal symmetries in SBT. Reflectivity results for light polarized in the ab plane show that the anisotropy in this plane is small in the frequency range f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
29
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 28 publications
6
29
0
Order By: Relevance
“…The roomtemperature spectrum above 200 cm Ϫ1 agrees with that in Ref. 16. The reflection bands are best resolved in the lowtemperature spectra where the mode dampings are smaller.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…The roomtemperature spectrum above 200 cm Ϫ1 agrees with that in Ref. 16. The reflection bands are best resolved in the lowtemperature spectra where the mode dampings are smaller.…”
supporting
confidence: 87%
“…The SM in the FE phase is expected to be active in both IR and Raman spectra. 16 Moret et al 16 reported IR reflectivity and transmission studies on FE SBT, but their work did not extend into the far-IR SM region. In the mid-IR, they found that the high-frequency ͑HF͒ modes in SBT showed the strong influence of the pseudotetragonal parent symmetry ͑e.g., approximate Raman IR mutual exclusion͒, but this will not extend to the symmetry-breaking SM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We proposed existence of an additional relaxation mode, which will slow down to T c1 and will cause dielectric anomaly near T c1 [9]. This relaxation we really observed in recent THz spectra below 300 K [14,16]. The aim of this paper is the continuation of the previous work at higher temperatures and to bring THz dielectric spectra of SBT thick film (same like in Ref.…”
Section: Introductionsupporting
confidence: 53%
“…Ferroelectric structure has space group A2 1 am (Z prim =2) and undergoes the phase transition (PT) to paraelectric phase at T c1 near 600 K. Recently was discovered intermediate tetragonal ferroelastic phase with Amam space group(Z prim =2) [7,8,9] which undergous to paraelectric paraelastic phase with I4/mmm (Z prim =1) structure above T c2 ≅ 770 K. This second phase transition is improper ferroelastic (with doubling of the primitive unit-cell volume on cooling) and the lower temperature one is proper ferroelectric (no multiplication of the primitive unit-cell volume with respect to the ferroelastic phase) [9]. The dynamics of the PT's in SBT has been investigated first by Raman scattering [10,11,12], later by Brillouin scattering [13] and Fourier transform infrared (FTIR) reflectivity and transmission spectroscopy [9,14,15]. It was shown that the lowest frequency optic phonon near 28 cm -1 (at 300 K) reduces its frequency on heating and even disappears from Raman spectra above T c1 due to the change of selection rules.…”
Section: Introductionmentioning
confidence: 99%